Front Cover: Photochemical CO2 Reduction Using Rhenium(I) Tricarbonyl Complexes with Bipyridyl‐Type Ligands with and without Second Coordination Sphere Effects (ChemPhotoChem 6/2021). Issue 6 (28th May 2021) - Rotundo, Laura; Grills, David C.; Gobetto, Roberto; Priola, Emanuele; Nervi, Carlo; Polyansky, Dmitry E.; Fujita, Etsuko
Abstract : The Front Cover illustrates the photocatalytic reduction of CO2 to CO by an aniline‐substituted Re‐bipyridine‐type photocatalyst in the presence of a strong electron donor (1, 3‐dimethyl‐2‐phenyl‐2, 3‐dihydro‐1H‐benzo[ d ]‐imidazole=BIH) in N, N ‐dimethylacetamide. This catalyst absorbs visible light intensely compared to related catalysts, and the presence of the aniline moiety has a beneficial effect on the photocatalytic activity. More information can be found in the Article by Carlo Nervi, Dmitry E. Polyansky, Etsuko Fujita and co‐workers .